สภาวะที่เหมาะสมที่สุดสําหรับการปรับปรุงเนื้อดินสโตนแวร์ - สิงห์คำ อายะชู (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Most of Stoneware body productions in the ceramic industries fired the body at high temperature (more than 1200 degree Celsius), which caused the high production cost of fuel. Most fuel’s production costs were 30% of all production costs. According to the Pareto Chart’s analysis, the firing temperature was found to be the main factor affecting the ceramic production cost. This independent study thus aimed to decrease the firing temperature of the stoneware body by determining the amount water absorption (value) and total shrinkage (value) according to the Industrial Standards. The research methodology consisted of Brainstorming, Pareto Chart, Cause and Effect Analysis, Cause and Effect Matrix, Fractional Factorial Design . After the brainstorming by using Fishbone diagram and Cause and Effect Matrix, the study found that 5 factors which decreased the firing temperature consisted of the Stoneware body’s firing temperature, Lampang kaolin, Lampang plastic clay, Borosilicate Frit, and the milling timing. So (the researcher made) the Fractional Factorial Experimental Design is of Resolution III, that was the Fractional Factorial Split-Plot Design consisting of the Hard-to-Change Factors; the firing temperature was at 1130 degree Celsius was used in this study. After the improvement of Stoneware body, the burning temperature could be decreased; it decreased from 1200 – 1250 degree Celsius to 1130 degree Celsius. (before the improvement) (The prior data comparing with the data) After the improvement, the result clearly showed the extremely decrease of production costs, which the percentages of the amount of water absorption v and total shrinkage met Industrial Standard of Stoneware body.